ANALISIS SENSITIVITAS PENURUNAN WAKTU PRODUKSI UNTUK MEMAKSIMALKAN PRODUK JADI SEKTOR KONSTRUKSI DENGAN MEMPERTIMBANGKAN KESEIMBANGAN LINTASAN - Rembulan, Glisina (Journal of Industrial and Engineering System, 2021)
In simple terms, optimal allocation of resources will undoubtedly increase production efficiency, which in turn will increase the company's profit. The track balance (Assembly Line Balancing/ALB) aims to distribute the workload among work stations. The object of this research is the balance of the production line and workload in the girder production process. This study emphasizes the sensitivity analysis on reducing working time. Sensitivity analysis was conducted to evaluate the parameters that affect operational flexibility and productivity levels. The decrease in processing time on the largest work element will affect the increase in output. In this case, the processing time on the work element waiting for dry cast will be reduced by 10 minutes in each scenario. In the 8th scenario, the processing time of the working elements waiting for the dry cast is 80 minutes. In other words, the resulting output is 6 units, while idle time drops to 150 minutes. This study recommends reducing the processing time of working elements waiting for dry cast to be 80 minutes.